Different β-glucans improve the growth performance and bacterial resistance in Nile tilapia - Pilarski, Fabiana [UNESP]; Ferreira de Oliveira, Carlos Alberto; Darpossolo de Souza, Fernanda Patrícia Brito; Zanuzzo, Fábio Sabbadin [UNESP] (Elsevier, 2017)
The role of glucan as a biologically active immunomodulator has been well documented for more than 40 years. However, the wide diversity of β-glucan forms and the extraction process has implications for the benefits of these compounds. Biorigin developed two samples of β-glucans using different biotechnological processes. Thus, in the present study, we fed Nile tilapia (Oreochromis niloticus) diets containing these two β-glucan molecules (BG01 and BG02) for 30 days prior to bacterial infection with Streptococcus agalactiae. The results showed that the different β-glucan samples exhibited biologically differently behaviors, but both increased the resistance against bacterial infection. Specifically, BG01 increased immunostimulation, while BG02 improved growth performance. In summary, these findings confirm the benefits of β-glucans in aquaculture and also provide further evidence of the growth promotion of these compounds.
Keywords: Fish; Glucans; Immunostimulant; Prebiotics